Some Useful Google Products for Online Library (LIS TODAY, 2022)
In this knowledge and information era, new technologies are emerging everyday which are enhancing  the quality of services provided by the library and information center and reducing the physical barriers.  Google was founded with the aim for organizing, disseminating and retrieving information / knowledge on the  Internet, in which it has been successful to a great extent. Google is continuously making efforts to build and  update its products and services to achieve the above stated objectives. At present, Google products play an  important role in improving the effectiveness and efficiency and of library and its services. This article  describes the Google products/services that are critical in providing library services and how they can be used  effectively by libraries. The article also describes how these products can be used by library professionals to  fulfill various functions and purposes of libraries and information centres.
Keywords: Google Products; Google Tools; Google Services; Blogger; Google Drive; Podcast